Safety (toxicity), pharmacokinetics, immunogenicity, and impact on elements of the normal immune system of recombinant human IL-15 in rhesus macaques - Waldmann, Thomas A. (American Society of Hematology, 2011)
IL-15 uses the heterotrimeric receptor IL-2/IL-15Rβ and the γ chain shared with IL-2 and the cytokine-specific IL-15Rα. Although IL-15 shares actions with IL-2 that include activation of natural killer (NK) and CD8 T cells, IL-15 is not associated with capillary leak syndrome, activation-induced cell death, or with a major effect on the number of functional regulatory T cells. To prepare for human trials to determine whether IL-15 is superior to IL-2 in cancer therapy, recombinant human IL-15 (rhIL-15) was produced under current good manufacturing practices. A safety study in rhesus macaques was performed in 4 groups of 6 animals each that received vehicle diluent control or rhIL-15 at 10, 20, or 50 μg/kg/d IV for 12 days. The major toxicity was grade 3/4 transient neutropenia. Bone marrow examinations demonstrated increased marrow cellularity, including cells of the neutrophil series. Furthermore, neutrophils were observed in sinusoids of enlarged livers and spleens, suggesting that IL-15 mediated neutrophil redistribution from the circulation to tissues. The observation that IL-15 administration was associated with increased numbers of circulating NK and CD8 central and effector-memory T cells, in conjunction with efficacy studies in murine tumor models, supports the use of multiple daily infusions of rhIL-15 in patients with metastatic malignancies.